Pengaruh Persepsi Kegunaan, Kepuasan Pengguna, Kesiapan Teknologi Informasi terhadap Minat Menggunakan E-Filing pada Wajib Pajak: Studi pada KPP Pratama Jambi Telanaipura - Raenando Raenando; Youdhi Prayogo; Achyat Budianto (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study aims to examine the effect of Perceived Usefulness, User Satisfaction and Information Technology Readiness on the interest in using e-filing among taxpayers. The data of this study uses primary data by distributing questionnaires to Individual Taxpayers registered at the Jambi Telanaipura City Tax Office. The sampling method of this study is simple sampling with a sample of 100 taxpayers. The data analysis method used in the study is multiple regression analysis assisted by the IBM SPSS statistic 27 application. The results of this study indicate that perceived usefulness has a positive effect on the interest use of e-filing, user satisfaction does not affect the use of e-filing, while information technology readiness has a positive effect on the use of e-filing. Simultaneously, the independent variables, namely perceived usefulness, user satisfaction and information technology readiness, affect the interest in using e-filing.